2021
DOI: 10.3390/smartcities4040069
|View full text |Cite
|
Sign up to set email alerts
|

Use of Machine Learning for Leak Detection and Localization in Water Distribution Systems

Abstract: This paper presents an investigation of the capacity of machine learning methods (ML) to localize leakage in water distribution systems (WDS). This issue is critical because water leakage causes economic losses, damages to the surrounding infrastructures, and soil contamination. Progress in real-time monitoring of WDS and ML has created new opportunities to develop data-based methods for water leak localization. However, the managers of WDS need recommendations for the selection of the appropriate ML methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…In contrast, the EPANET hydraulic model of the University of Port Harcourt Choba campus is shown in Figure 1. The water distribution network was split into two zones: Zone 1 (LZ1), which contains eight candidate nodes, and Zone 2 (LZ2), which contains seven candidate nodes [15]. The water distribution network was split into two zones: Zone 1 (LZ1), which contains eight candidate nodes, and Zone 2 (LZ2), which contains seven candidate nodes [15].…”
Section: Data Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the EPANET hydraulic model of the University of Port Harcourt Choba campus is shown in Figure 1. The water distribution network was split into two zones: Zone 1 (LZ1), which contains eight candidate nodes, and Zone 2 (LZ2), which contains seven candidate nodes [15]. The water distribution network was split into two zones: Zone 1 (LZ1), which contains eight candidate nodes, and Zone 2 (LZ2), which contains seven candidate nodes [15].…”
Section: Data Generationmentioning
confidence: 99%
“…The water distribution network was split into two zones: Zone 1 (LZ1), which contains eight candidate nodes, and Zone 2 (LZ2), which contains seven candidate nodes [15]. The water distribution network was split into two zones: Zone 1 (LZ1), which contains eight candidate nodes, and Zone 2 (LZ2), which contains seven candidate nodes [15]. The emitter coefficient used in the simulation of leak occurrence in the nodes is based on the classical Torricelli equation for flow through an orifice.…”
Section: Data Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam beberapa penelitian yang telah dilakukan untuk mendeteksi kebocoran pipa menggunakan algoritma Support Vector Machine (SVM) [1][2]. Ada juga beberapa peneliti yang menggunakan Neural Network dalam mendeteksi kebocoran pipa [3]. Penelitian selanjutnya menggunakan data time series tekanan dan volume air dan metode regresi sebagai algoritmanya [4], ada pula peneliti dalam deteksi kebocoran pipa dan lokasinya menggunakan metode berbasis fuzzy [5], maupun penggunaan metode K-Nearest Neighboor [6].…”
Section: Pendahuluanunclassified
“…Researchers of this study proposed a data based leak detection model for leak identification that showed a good result and has an accuracy of 90% at all points except singularities by the confusion matrix method (3) . Researchers of this study represent an investigation of the capacity of six machine learning methods presented by the data generated using EPANET software, indicate that the supervised logistic regression and random forest method performed well to localize the leakage (4) . A multi-strategy ensemble learning(MEL) was presented in this research as an effective solution for an improvement in leak detection using acoustic techniques (5) .…”
Section: Introductionmentioning
confidence: 95%